A new insular species of Rock Gecko (Cnemaspis Boulenger) from Pulau Langkawi, Kedah, Peninsular Malaysia - Grismer, L. Lee; Wood, P. L. Jr.; Quah, Evan S. H.; Anuar, Shahrul; Ngadi, Ehwan; Ahmad, Norhayati (Zootaxa, 2015)
A new, diminutive species of Rock Gecko Cnemaspis mahsuriae sp. nov. of the affinis group, is described from Gunung Raya on Pulau Langkawi, Kedah, Peninsular Malaysia and is differentiated from all other species in the affinis group by having a unique combination of characters including a maximum SVL of 36.6 mm; keeled subtibials and ventrals; 21–24 paravertebral tubercles; no tubercles in the lateral caudal furrows; caudal tubercles not encircling tail; no precloacal pores; 23–26 subdigital lamellae on the fourth toe; no white ocelli in the shoulder region; no yellow postscapular band; and faint yellow bars on the flanks. Cnemaspis mahsuriae sp. nov. is a forest-dwelling species living in close sympatry or paraptry with the insular endemic C. roticanai Grismer & Chan. The Langkawi Archipelago harbors a unique mix of Malaysian and Indochinese taxa and the frequency of new discoveries from this group of islands is increasing.